2001
DOI: 10.1177/073428290101900303
|View full text |Cite
|
Sign up to set email alerts
|

Is the Revised Psychopathy Checklist Clinically Useful for Adolescents?

Abstract: Recent studies have provided evidence for the reliability and validity of Hare's Psychopathy Checklist, Revised (PCL-R) for forensic samples. The present study investigated PCL-R psychometric properties among Caucasian and African-American adolescent males from forensic and school settings. The clinical utility of the PCL-R was investigated in terms of predicting future delinquency above and beyond data that are more readily available. Good reliability and validity for the PCL-R were found. PCL-R Total and Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 28 publications
0
31
0
2
Order By: Relevance
“…Psychopathy has shown undeniable links to violent and aggressive behavior in both adults and adolescents [Vitacco and Vincent, 2006]. Studies using the most valid and reliable indicator of psychopathic traits, the Psychopathy Checklist: Youth Version [PCL:YV; Forth et al, 2003] have found it to be strongly related to both general and violent recidivism [e.g., Catchpole and Gretton, 2003;Ridenour et al, 2001]. In retrospective follow-backs, the PCL:YV was related to violent behavior at both 5-year [Gretton et al, 2001] and 10-year periods [Gretton et al, 2004].…”
Section: The Roles Of Callousness and Psychopathy In Understanding VImentioning
confidence: 99%
“…Psychopathy has shown undeniable links to violent and aggressive behavior in both adults and adolescents [Vitacco and Vincent, 2006]. Studies using the most valid and reliable indicator of psychopathic traits, the Psychopathy Checklist: Youth Version [PCL:YV; Forth et al, 2003] have found it to be strongly related to both general and violent recidivism [e.g., Catchpole and Gretton, 2003;Ridenour et al, 2001]. In retrospective follow-backs, the PCL:YV was related to violent behavior at both 5-year [Gretton et al, 2001] and 10-year periods [Gretton et al, 2004].…”
Section: The Roles Of Callousness and Psychopathy In Understanding VImentioning
confidence: 99%
“…Although researchers have begun to test the predictive utility of the PCL-YV with male adolescents (Forth & Burke, 1998;Ridenour, Marchant, & Dean, 2001) and adult women (Forth, 1996;Rutherford, Cacciola, Alterman, & McKay, 1996: Salekin, Rogers, Ustad, & Sewell, 1998, there are no published studies of recidivism among female adolescents. As previously noted, experts in risk assessment have stated that male-based instruments are likely to function similarly within female populations (Hare, 1991;Webster, 1999).…”
Section: Can Psychopathy Inform the Prediction Of Future Offending Ammentioning
confidence: 99%
“…A number of studies using the Psychopathy Checklist: Youth Version (PCL:YV; Forth, Kosson, & Hare, 2003) have reported similar psychometric properties to the PCL-R (Hare, 1991) and found that male juveniles scoring high on the PCL:YV are similar to adult male psychopaths with respect both to psychological correlates and behavioral characteristics (see Vincent & Hart, 2002, for a review). The PCL-YV has also demonstrated predictive utility within short-term prospective studies of male adolescents (Forth, Hart, & Hare, 1990;Ridenour, Marchant, & Dean, 2001). However, a review of published PCL-YV studies indicates that only 6 of the 34 studies completed to date have included females, with sample sizes ranging from 11 to 80 females (Forth et al, 2003).…”
Section: What Does Research With Boys Tell Us About the Prediction Ofmentioning
confidence: 99%